Analysis of Creation Central Agropolitan Through Aglomerative Region Planning in Lampung Province - Zulfikar, Iwan (International Journal of Economics, Business, and Entrepreneurship, 2019)
Rural areas in Indonesia generally have the potential for agriculture but there is little industrial sector orientation, especially in the agricultural product processing sector. For this reason, it is necessary to integrate the sectoral and regional planning through the formulation of a development strategy by considering several basic conditions (local potential) so that each stage of development will be clear. Therefore it is necessary to formulate, whether in Lampung Province in the Regency can form a small city by determining the region of the agglomerative hierarchy through the region and the base sector to support the regency agropolitan center. Analyzing is done by using the gravity area method to see regional strength (the strongest regency/city) with an indication of the population, GRDP and also the distance between regencies/cities in Lampung Province. Then to see the strength of the base sector will be done by the LQ method and Input-Output with the expectation of the model used (gravity analysis) that the Agropolitan center can be determined while the LQ and Input-Output models will determine the strength of the "Agro" base sector so that the Regional and Sectoral analysis will the acceleration of regional agglomeration in Lampung Province is seen.